EKSPERIMENTASI PEMBELAJARAN MATEMATIKA DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENTS DAN TEAMS ASSISTED INDIVIDUALIZATION PADA MATERI POKOK BANGUN RUANG SISI DATAR DITINJAU DARI MOTIVASI BERPRESTASI SISWA KELAS VIII SMP - Mishbahul Huda; Tri Atmojo Kusmayadi; Budi Usodo (Journal of Mathematics and Mathematics Education, 2015)
Abstract: The objectives of this research are to investigate: (1) which learning model of the cooperative learning model of the TGT type, the cooperative learning model of the TAI type, and the direc learning model results in a better learning achievement in Mathematics; (2) which students of the the students with the high achievement motivation, the students with the moderate achievement motivation, and the students with the low achievement motivation have a better learning achievement in Mathematics; (3) in each category of the achievement motivations, which learning model of the cooperative learning model of the TGT type, the cooperative learning model of the TAI type, and the direc learning model results in a better learning achievement in Mathematics; and (4) in each learning model, which students of the the students with the high achievement motivation, the students with the moderate achievement motivation, and the students with the low achievement motivation have a better learning achievement in Mathematics. This research used the quasi experimental research method with the factorial design of 3x3. Its population was the students in Grade VIII of State Junior Secondary Schools of Wonogiri regency in Academic Year 2013/2014. The samples of the research were taken by using the stratified cluster random sampling technique. The samples of the research were the students as many as 299 of State Junior Secondary School 1 of Purwantoro, State Junior Secondary School 1 of Jatisrono, and State Junior Secondary School 2 Puhpelem. The data of the research were analyzed by using the two-way analysis of variance (ANOVA) with unbalanced cells at the significance level of 5%. The results of the research are as follows: 1) the students instructed with the cooperative learning model of the TGT type have a better learning achievement in Mathematics as those instructed with the cooperative learning model of the TAI type and direct learning model, the students instructed with the cooperative learning model of the TAI type have a better learning achievement in Mathematics as those instructed with the direct learning model. 2) The students with the high achievement motivation have a better learning achievement in Mathematics as those with the moderate achievement motivation and low achievement motivation, the students with the high achievement motivation have a better learning achievement in Mathematics than those with the low achievement motivation. 3) In each category of the achievement motivations, the students instructed with the cooperative learning model of the TGT type have a better learning achievement in Mathematics as those instructed with the cooperative learning model of the TAI type and direct learning model, the students instructed with the cooperative learning model of the TAI type have a better learning achievement in Mathematics as those instructed with the direct learning model. 4) In each learning model, the students with the high achievement motivation have a better learning achievement in Mathematics as those with the moderate achievement motivation and low achievement motivation, the students with the moderate achievement motivation have a better learning achievement in Mathematics as those with the low achievement motivation.Keywords: The cooperative learning model of the TGT type, the cooperative learning model of the TAI type, direct learning, and achievement motivation.